Wakaf Produktif: Inovasi Filantropi Terhadap Interkoneksi Bank Umum Syariah (BUS) Untuk Masa Depan Ekonomi Islam - Kholis, Akhmad Nur; Zubaeri, Ahmad; Sangadah, Umi (LABATILA : Jurnal Ilmu Ekonomi Islam, 2024)
This research focuses on the management and development of productive waqf through an interconnected pattern between Islamic Commercial Banks (BUS) and Islamic Philanthropic Institutions at Bank Syariah Indonesia (BSI) and BSI Maslahat. This research is based on 3 questions, there are: (1) what is the interconnection pattern of Islamic Banks with Nadzir Institutions in the development of productive waqf?; (2) what is the significance of the management and development of productive waqf in Islamic Banks with the Nadzir Institution?; and (3) is it possible for waqf funds to become funding for strengthening Islamic Bank assets? There are 2 sources of data used in this study, namely: (1) data in the form of documents in the form of financial reports, company websites, and other supporting documents; and (2) interview data with respondents. The data that has been obtained, then analyzed using qualitative analysis using the Miles & Huberman interactive model. Referring to the research questions, answers were obtained, including: (1) the pattern of interconnection that occurs between Bank Syariah Indonesia (BSI) and BSI Maslahat is a symbiotic interconnection of mutualism; (2) Islamic banks must actively control waqf management carried out by nadzirs; and (3) cash waqf can be an instrument to increase the liquidity of Islamic Banks